Casein kinase 1 family regulates PRR5 and TOC1 in the Arabidopsis circadian clock - Uehara, Takahiro N; Mizutani, Yoshiyuki; Kuwata, Keiko; Hirota, Tsuyoshi; Sato, Ayato; Mizoi, Junya; Takao, Saori; Matsuo, Hiromi; Suzuki, Takamasa; Ito, Shogo; Saito, Ami N; Nishiwaki-Ohkawa, Taeko; et al. (Proceedings of the National Academy of Sciences - PNAS, 2019)
The circadian clock provides organisms with the ability to adapt to daily and seasonal cycles. Eukaryotic clocks mostly rely on lineage-specific transcriptional-translational feedback loops (TTFLs). Posttranslational modifications are also crucial for clock functions in fungi and animals, but the posttranslational modifications that affect the plant clock are less understood. Here, using chemical biology strategies, we show that the CASEIN KINASE 1 LIKE (CKL) family is involved in posttranslational modification in the plant clock. Chemical screening demonstrated that an animal CDC7/CDK9 inhibitor, PHA767491, lengthens the circadian period. Affinity proteomics using a chemical probe revealed that PHA767491 binds to and inhibits multiple CKL proteins, rather than CDC7/CDK9 homologs. Simultaneous knockdown of CKL-encoding genes lengthened the circadian period. CKL4 phosphorylated transcriptional repressors PSEUDO-RESPONSE REGULATOR 5 (PRR5) and TIMING OF CAB EXPRESSION 1 (TOC1) in the TTFL. PHA767491 treatment resulted in accumulation of PRR5 and TOC1, accompanied by decreasing expression of PRR5- and TOC1-target genes. A double mutant was hyposensitive to PHA767491-induced period lengthening. Together, our results reveal posttranslational modification of transcriptional repressors in plant clock TTFL by CK1 family proteins, which also modulate nonplant circadian clocks.